Tumor size and prognosis in patients with Wilms tumor - Valentina Oliveira Provenzi; Rafael Fabiano Machado Rosa; Rosana Cardoso Manique Rosa; Adriana Vial Roehe; Pedro Paulo Albino dos Santos; Fabrízia Rennó Sodero Faulhaber; Ceres Andréia Vieira de Oliveira; Paulo Ricardo Gazzola Zen (Sociedade de Pediatria de São Paulo, 2015)
OBJECTIVE: Investigate the relationship of the tumor volume after preoperative chemotherapy (TVAPQ) and before preoperative chemotherapy (TVBPQ) with overall survival at two and at five years, and lifetime. METHODS: Our sample consisted of consecutive patients evaluated in the period from 1989 to 2009 in an Onco-Hematology Service. Clinical, histological and volumetric data were collected from the medical records. For analysis, chi-square, Kaplan-Meier, log-rank and Cox regression tests were used. RESULTS: The sample consisted of 32 patients, 53.1% were male with a median age at diagnosis of 43 months. There was a significant association between TVAPQ>500mL and the difference between the TVBPQ and TVAPQ (p=0.015) and histologic types of risk (p=0.008). It was also verified an association between the difference between the TVBPQ and TVAPQ and the predominant stromal tumor (p=0.037). When assessing the TVAPQ of all patients, without a cutoff, there was an association of the variable with lifetime (p=0.013), i.e., for each increase of 10mL in TVAPQ there was an average increase of 2% in the risk of death. CONCLUSIONS: Although our results indicate that the TVAPQ could be considered alone as a predictor of poor prognosis regardless of the cutoff suggested in the literature, more studies are needed to replace the histology and staging by tumor size as best prognostic variable.